2020
DOI: 10.3390/metabo10030109
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Phenotypes of Hypoxic-Ischemic Encephalopathy with Normal vs. Pathologic Magnetic Resonance Imaging Outcomes

Abstract: Hypoxic-Ischemic Encephalopathy (HIE) is one of the most relevant contributors to neurological disability in term infants. We hypothesized that clinical outcomes of newborns with (HIE) can be associated with changes at plasma metabolic level enabling the detection of brain injury. Plasma samples of a cohort of 55 asphyxiated infants who evolved to moderate/severe HIE were collected between birth and completion of therapeutic hypothermia (TH). Samples were analyzed employing a quantitative gas chromatography–ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Pyruvate levels did not however predict the severity of the grade of asphyxia, as the authors could not find a significant difference between neonates presenting with mild, moderate and severe HIE (Sarnat 3) compared to the control group. Even in the HYPOTOP trial, the analysis of pyruvate cord blood levels among neonates presenting with HIE and treated with TH, did not identify and differentiate those with pathological brain MRI findings (46). There were higher pyruvate levels 48 h after the administration of topiramate in neonates presenting with HIE and treated with TH, in comparison to the control group.…”
Section: Pyruvate Blood Levelsmentioning
confidence: 92%
See 1 more Smart Citation
“…Pyruvate levels did not however predict the severity of the grade of asphyxia, as the authors could not find a significant difference between neonates presenting with mild, moderate and severe HIE (Sarnat 3) compared to the control group. Even in the HYPOTOP trial, the analysis of pyruvate cord blood levels among neonates presenting with HIE and treated with TH, did not identify and differentiate those with pathological brain MRI findings (46). There were higher pyruvate levels 48 h after the administration of topiramate in neonates presenting with HIE and treated with TH, in comparison to the control group.…”
Section: Pyruvate Blood Levelsmentioning
confidence: 92%
“…In terms of prognosis, Frey et al showed that asphyxiated neonates who died during the first week of life had significantly higher lactate levels than those presenting with more mild neurological deficits (45). Pineiro-Ramos et al however, could not demonstrate a relation between the cord blood lactate levels of neonates presenting with HIE and the severity of pathological cerebral magnetic resonance imaging (MRI) performed between day 4 and 8 of life (46). Ahearne et al also showed that cord blood lactate levels in asphyxiated neonates did not predict outcome at 3 years of age (47).…”
Section: Blood Levelsmentioning
confidence: 99%
“…Metabolomics can also provide valuable information for outcome prediction. Metabolites offer a unique signature potentially usable to predict neonatal diseases and evaluate disease progression and treatments' effect (156)(157)(158).…”
Section: (Epi)genetics and Omics-futurementioning
confidence: 99%
“…A new study [ 3 ] evaluating early evolving blood metabolome provides, for the first time, useful data to identify newborns who will show pathologic Magnetic Resonance Imaging (MRI) patterns after TH. The authors demonstrated changes of purines (i.e., xanthine and xanthosine), as well as of the steroid hormone biosynthesis pathway, in newborns with pathologic MRI outcomes in blood samples drawn before the initiation of TH during the whole study period.…”
Section: Hypoxic–ischemic Encephalopathy (Hie)mentioning
confidence: 99%